2013
DOI: 10.1158/1078-0432.ccr-12-2380
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging Reveals a Role for AKT in Resistance to Cisplatin for Ovarian Endometrioid Adenocarcinoma

Abstract: Purpose Ovarian cancer is the fifth leading cause of cancer deaths among American women. Platinum-based chemotherapy, such as cisplatin, represents the standard of care for ovarian cancer. However, toxicity and acquired resistance to cisplatin have proven challenging in the treatment of ovarian cancer patients. Experimental Design Using a genetically engineered mouse (GEM) model of ovarian endometrioid adenocarcinoma (OEA) in combination with molecular imaging technologies, we studied the activation of the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Further it has been reported that activation of the PI3K/ Akt pathway is involved in acquired resistance (Sunters et al, 2003;Zhong et al, 2010;Wang et al, 2013). Observations of our study showed significantly upregulation of PTEN with markedly down-regulated expression of Akt, mTOR and p-GSK3β.…”
Section: Discussionsupporting
confidence: 65%
“…Further it has been reported that activation of the PI3K/ Akt pathway is involved in acquired resistance (Sunters et al, 2003;Zhong et al, 2010;Wang et al, 2013). Observations of our study showed significantly upregulation of PTEN with markedly down-regulated expression of Akt, mTOR and p-GSK3β.…”
Section: Discussionsupporting
confidence: 65%
“…Similar to previous reports (19), relatively lower doses of drugs, that is, 2.5 mg/kg DDP or 5 mg/kg Taxol, were given via the tail vein after the tumor diameters reached 0.5 cm, and the drugs were administered once every 4 days. Similar to the results obtained in vitro, the silencing of CABYR-a/b alone significantly delayed tumor growth and decreased the total weight of the tumors in H460 xenografts compared with control animals, and these inhibitory effects were increased when the mice were treated with DDP or Taxol.…”
Section: Cabyr-a/b Knockdown Increases Tumor Sensitivity To Ddp and Tmentioning
confidence: 89%
“…Murine ovarian endometrioid adenocarcinoma cell lines were derived as previously described (18). Briefly, the W2476T tumor cell line was established by mechanically dispersing ovarian tumor tissues with sterile scalpels followed by digestion at 37° C with 0.05% Trypsin-EDTA for 20 minutes.…”
Section: Methodsmentioning
confidence: 99%